Association of physical fitness on self- perceived work ability on working aged people - Kaarna, Jesse (2016)
Ageing population combined with plans of lengthen careers compel both organizations and occupational healthcare system to renew. Sufficient physical fitness is one of the key factors to pursuit this goal which enables workers to continue in the working life. Aim of the study was to clarify association of physical fitness on self- perceived work ability on working aged people by utilizing Laturi Energy Index and short version of Work Ability Index (WAP) questionnaire in a working age population. Study was a sub-study of a larger ALIWO research project.